Psychiatric comorbidities among patients of Prurigo nodularis: A cross sectional study in tertiary care hospital south India - Soumya G Hegde; YR Niranjan Hebbar; Swathi (Our Dermatology Online, 2023)
Background: Prurigo nodularis (PN) is a dermatologic itchy condition which affects the normal day to day life activities. Due to its chronic condition psychiatric comorbidities are regularly seen in these patients. Due to scarcity of literature in Indian background this study was conducted in our tertiary care centre. Materials and methodology: It was a descriptive, cross sectional study conducted at department of dermatology during May 2021 to April 2022 where all diagnosed PN patients were screened for psychiatric comorbidities using MINI- International Neuropsychiatric interview. Results: We found Generalised Anxiety Disorder among 27.2% and Major Depressive Disorder among 15.8% of study population. Also Social phobia among 16.8% of males. Majority of 61% in both males and females didn't had any psychiatric disorders in our study sample. Conclusion: Higher incidences of anxiety, depressio